International prospective observational study of upper gastrointestinal haemorrhage: Does weekend admission affect outcome?. Issue 8 (1st December 2017) - Murray, Iain A; Dalton, Harry R; Stanley, Adrian J; Ngu, Jing H; Maybin, Brian; Eid, Mahmoud; Madsen, Kenneth G; Abazi, Rozeta; Ashraf, Hamad; Abdelrahim, Mohamed; Lissmann, Rebecca; Herrod, Jenny; et al.
Abstract : Introduction: Out of hours admissions have higher mortality for many conditions but upper gastrointestinal haemorrhage studies have produced variable outcomes. Methods: Prospective study of 12 months consecutive admissions of upper gastrointestinal haemorrhage from four international high volume centres. Admission period (weekdays, weeknights or weekends), demographics, haemodynamic parameters, laboratory results, endoscopy findings, further procedures and 30‐day mortality were recorded. Five upper gastrointestinal haemorrhage risk scores were calculated. Results: 2118 patients, 60% male, median age 66 years were studied. Compared with patients presenting on weekdays, patients presenting at weekends had no significant differences in comorbidity, pulse, systolic BP, risk scores, frequency of peptic ulcers or varices. Those presenting on weekdays had lower haemoglobin ( p  = 0.007) and were more likely to have a normal endoscopy ( p  < 0.01). Time to endoscopy was less for weeknight presentation ( p  = 0.001). Sixty‐seven per cent of those presenting on weekdays, 75% on weeknights and 60% at weekends had endoscopy within 24 h. Transfusion requirements, need for endoscopic therapy or surgery/embolization, rebleeding rates (6.1%) and mortality (7.2%) did not differ with presentation time. Conclusion: This multi‐centre international study in large centres found no difference in demographics, comorbidity or haemodynamic stability and no increase in mortality for patients presenting with upper gastrointestinal haemorrhage out of hours.